Arabic instruction in Israel : lessons in conflict, cognition and failure - Uhlmann, Allon J. (Social, Economic and Political Studies of the Middle East and Asia, 2017)
In Arabic Instruction in Israel Allon J. Uhlmann confronts two conundrums, namely the persistently poor level of Arabic proficiency among Jewish Arabic students and teachers, and the traumatic alienation of Arab students by university Arabic grammar instruction. These are not aberrations but rather direct, albeit unintended, systemic consequences of the field of Arabic instruction, where Jewish students encounter Arabic as a dead, hostile language; Jewish hegemony devalues native Arabic proficiency; and Arab students are locked into a fractured educational trajectory - encountering two alienating and mutually unintelligible grammars of Arabic at school and at university. By tracing systemic variabilities in cognition and learning Uhlmann exposes hitherto misrecognised dynamics that hinder Arabic instruction in Israel, thereby offering new avenues for possible change.